A Study on Digital economic development and its impact on Indian Economy - Vibha Suraj Bhusari (AG Volumes, 2022)
As one of the fastest-growing economies in the world, India is also firmly entrenched in digital technology. In underdeveloped nations, the digital economy is gaining traction at a rapid rate. Increasing internet penetration, quick technology adoption, and high sales of technological devices such as smart phones, tablets, and other similar products have led to an appealing online consumer base and unparalleled expansion of digitization in India. It is essential to integrate the economy through building digital marketplaces because of the role of digitization in today's environment. The three main advantages a country gets from its economy are businesses, pricing, and productivity. According to international studies, businesses that make use of the internet see a boost in profitability of 10% on average. A total of 3.2 % of India's GDP is generated by internet-related businesses. The digital contributions of various nations and the jobs generated as a result of the rise in digitization. The growth of small and medium-sized enterprises (SMEs) would be a significant source of new jobs and a significant contributor to online commerce. India is one of the world's fastest-growing countries, with a large proportion of its population (65 %) under the age of 35. It is only when individuals are able to comprehend and implement these changes that we will be able to see the full impact of digitalization. In order to do so, each person will need to have a basic grasp of finance, which will enable them to make sound choices. Considering that all financial transactions will be conducted online as a result of digitalization, financial literacy in the digital age has become an important skill.